Supersessionism and the Cult Attitude of Stephen and Hebrews - Moore, Nicholas J. (Irish theological quarterly, 2024)
In the face of continued debates about Christian supersessionism with regard to Judaism, this article revisits two texts which have been thought to display the harshest anti-temple attitudes in the New Testament: Stephen’s speech in Acts 7, and the Letter to the Hebrews. Many scholars believe these two texts are connected, and a perceived anti-cultic attitude forms one of the key alleged similarities between the two. The article first examines shared lexical and conceptual points between the two texts, affirming their proximity. It then examines each text’s cult attitude in turn. Stephen portrays the temple as divinely given yet always subordinate to God’s heavenly presence. Hebrews frames deficiencies in the Levitical cultus as divinely intended in light of the heavenly tabernacle. These texts therefore do not condemn but instead relativize Israel’s earthly sanctuary/ies, in keeping with themes in Israel’s Scriptures, and thus should not be regarded as supsersessionist.